Faecal immunochemical testing for adults with symptoms of colorectal cancer attending English primary care: a retrospective cohort study of 14 487 consecutive test requests. Issue 6 (17th July 2020) - Nicholson, Brian D.; James, Tim; Paddon, Maria; Justice, Steve; Oke, Jason L.; East, James E.; Shine, Brian
Summary: Background: Faecal immunochemical testing (FIT) is recommended by the National Institute for Health and Care Excellence (NICE) to triage symptomatic primary care patients for further investigation of colorectal cancer. Aim: To ascertain the diagnostic performance of FIT in symptomatic adult primary care patients. Methods: Faecal samples from routine primary care practice in Oxfordshire, UK were analysed using the HM‐JACKarc FIT method between March 2017 and March 2020. Clinical details were recorded. Patients were followed for up to 36 months in linked hospital records for evidence of benign and serious (colorectal cancer, high‐risk adenomas and bowel inflammation) colorectal disease. The diagnostic accuracy of FIT is reported by gender, age group and FIT threshold. Results: In 9896 adult patients with at least 6‐month follow‐up, a FIT result ≥10 µg Hb/g faeces had a sensitivity for colorectal cancer of 90.5% (95% CI 84.9%‐96.1%), specificity 91.3% (90.8%‐91.9%), positive predictive value (PPV) 10.1% (8.15%‐12.0%) and negative predictive value (NPV) 99.9% (99.8%‐100.0%). The PPV and specificity for serious colorectal disease were higher and the sensitivity and NPV lower than for colorectal cancer alone. The area under the curve for all adults did not change substantially by gender or by increasing the minimum age of testing. Using ≥10 µg Hb/g faeces, 10% of adults would be investigated to detect 91% of cancers, a number needed to scope of ten to detect one cancer. Using ≥7, ≥50 and ≥150 µg Hb/g faeces, 11%, 4% and 3% of adults would be investigated, and 91%, 74% and 54% cancers detected, respectively. Conclusion: A FIT threshold of ≥10 µg Hb/g faeces would be appropriate to triage adult patients presenting to primary care with symptoms of serious colorectal disease. FIT may be used to reprioritise patients referred with colorectal cancer symptoms whose investigations have been delayed by the COVID‐19 pandemic.